PERAN PETUGAS KOLEKTOR DESA DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB-P2) DI KABUPATEN SUBANG - Roheman, Iman; Anita, Dian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research is motivated by the level of taxpayer compliance in paying Land and Building Tax, the lack of coordination between village collector officers and the Regional Revenue Agency, and the low performance in collecting Land and Building Taxes. The method in this study uses qualitative research. Primary data sources are 10 people. Data collection techniques in this study using interviews, observation and documentation. The data analysis technique uses data reduction, data presentation and drawing conclusions or verification. Test the validity of the data in this study using prolonged observation of increased persistence and triangulation. The results obtained in this study, the role of village collector officers in improving taxpayer compliance in paying PBB taxes in Subang District, Jalancagak District and Subang District has been implemented but not maximized. Not maximized based on the obstacles that occur, both internal and external obstacles. Internal obstacles include the lack of awareness of taxpayers in paying land and building taxes, lack of understanding of land and building taxes, lack of understanding of the main duties and functions of village collector officers and the economic condition of taxpayers. Meanwhile, external constraints include, where the tax subject is not known to the officer, the contents of the data are not in accordance with the tax object owned, multiple tax returns (SPPT) and regional expansion. The strategic efforts carried out are by providing counseling or socialization, increasing the level of land and building tax services and providing sanctions so that the achievement of the target of land and building tax revenue can be achieved.